Implementasi Pembelajaran Aspek Kognitif Mengenal Lambang Bilangan pada Anak Usia Dini di Sentra Persiapan - Sri Wulandari; Suwahono (ABNA : Journal of Islamic Early Childhood Education, 2020)
The problem in this research is that early childhood cognitive development is still lacking due to monotonous learning. The research objective was to determine the level of cognitive development through the introduction of number symbols. This research is a descriptive qualitative type. Research setting at PGIT Al Firdaus Nogosari, Boyolali from July to September 2020. The research subjects were center teachers, principal informants and students. Collecting data using observation, interviews and documentation. The data validity technique used data triangulation technique. Data analysis techniques used data collection, data reduction, data presentation and drawing conclusions. The conclusion of the implementation of learning on the cognitive aspect of recognizing the symbol of numbers in the preparation center consists of 1. Learning planning by compiling Prota, Prosem, RPPM and RPPH. 2. Implementation of learning by introducing number symbols, counting using fingers, and connecting objects with a number symbol, closing activities are carried out by recalling. 3. The assessment is carried out using the child's daily assessment and anecdotal notes.